Antimicrobial Activity and Resistance: Influencing Factors - Li, Jun; Xie, Shuyu; Ahmed, Saeed; Wang, Funan; Gu, Yufeng; Zhang, Chaonan; Chai, Ximan; Wu, Yalan; Cai, Jinxia; Cheng, Guyue (Frontiers in Pharmacology, 2017)
Rational use of antibiotic is the key approach to improve the antibiotic performance and tackling of the antimicrobial resistance. The efficacy of antimicrobials are influenced by many factors: (1) bacterial status (susceptibility and resistance, tolerance, persistence, biofilm) and inoculum size; (2) antimicrobial concentrations (mutant selection window and sub-inhibitory concentration); (3) host factors (serum effect and impact on gut micro-biota). Additional understandings regarding the linkage between antimicrobial usages, bacterial status and host response offers us new insights and encourage the struggle for the designing of antimicrobial treatment regimens that reaching better clinical outcome and minimizing the emergence of resistance at the same time.